Digital identity and privacy: how technologies change subjectivity - P.J.Aslamkulova; S.Dj.Ibragimova; M.V.Abdullayeva (Science and Education, 2026)
The rapid digitalization of contemporary society has transformed not only communication and economic relations but also the very structure of human subjectivity. Identity, once grounded in stable social roles, embodied interaction, and long-term personal narratives, today becomes increasingly mediated by technological systems. Digital platforms - from social networks to algorithmic governance - reshape how individuals understand themselves, how others perceive them, and how personal information circulates. This article explores how digital identity is formed, how privacy becomes a contested territory, and how technological environments influence the constitution of the modern subject.